Hubungan Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Pasien Di Rumah Sakit - Aribowo, Kornelis; Purwanda, ⁠Eka; Rahmi, Afriyeni Sri (Cattleya Darmaya Fortuna, 2024)
Quality health services are an important factor in increasing patient satisfaction and loyalty. The 1945 Constitution of the Republic of Indonesia affirms the right of the community to get adequate health services, which is the responsibility of local and central governments. Hospitals as the main healthcare providers must meet the expectations of patients not only in terms of treatment but also service experience. This study examines the relationship between service quality, satisfaction, and patient loyalty in hospitals. With increasing competition in the healthcare sector, hospitals must improve the quality of services to retain patients. The study also highlights external factors such as cost, accessibility, and socioeconomic conditions that influence patients' responses to service quality. The results of the research are expected to provide insight for hospital management to formulate better policies and programs, so that the services provided continue to improve and create patient satisfaction and loyalty.